Presence accounted for? student-teachers establishing and experiencing presence in synchronous online teaching environments. Issue 1 (2nd January 2022) - Donlon, Enda; Conroy Johnson, Marie; Doyle, Audrey; McDonald, Elaine; Sexton, P. J.
ABSTRACT: In Ireland, as around the world, the Covid-19 pandemic necessitated that Higher Education Institutions (HEIs) adopt innovative approaches to ensure the continuity of placement-related components of Initial Teacher Education (ITE) programmes. One post-primary concurrent ITE programme conceptualised and developed the Teaching Online Programme (TOP), a multifaceted initiative to introduce student-teachers to the theory and practice of synchronous and asynchronous online teaching via a structured and tutor-supported online peer-teaching experience. Drawing upon the Community of Inquiry framework as a lens, this paper considers how pre-service student-teachers facilitated and experienced 'teaching presence' while peer-teaching in a synchronous online environment as part of their TOP. The paper finds that design and organisation, facilitating discourse, and direct instruction, were viewed as relevant and helpful for teaching in online settings, and that overall there was agreement about the importance of establishing a strong sense of teacher presence when teaching in synchronous videoconferencing environments such as Zoom. It concludes by considering how these findings may be of relevance for future development of ITE programmes.